Creating Lithium‐Ion Electrolytes with Biomimetic Ionic Channels in Metal–Organic Frameworks. Issue 23 (30th April 2018) - Shen, Li; Wu, Hao Bin; Liu, Fang; Brosmer, Jonathan L.; Shen, Gurong; Wang, Xiaofeng; Zink, Jeffrey I.; Xiao, Qiangfeng; Cai, Mei; Wang, Ge; Lu, Yunfeng; Dunn, Bruce
Abstract: Solid‐state electrolytes are the key to the development of lithium‐based batteries with dramatically improved energy density and safety. Inspired by ionic channels in biological systems, a novel class of pseudo solid‐state electrolytes with biomimetic ionic channels is reported herein. This is achieved by complexing the anions of an electrolyte to the open metal sites of metal–organic frameworks (MOFs), which transforms the MOF scaffolds into ionic‐channel analogs with lithium‐ion conduction and low activation energy. This work suggests the emergence of a new class of pseudo solid‐state lithium‐ion conducting electrolytes. Abstract : A novel class of lithium‐ion conducting electrolytes by complexing perchlorate anions to the open metal sites of metal–organic frameworks is reported, resulting in negatively charged ionic channels analogous to the ionic channels in biological systems. Such biomimetic ionic channels allow rapid transport of lithium ions with low activation energy.